The Effect of PMSE Tax Policy, Tax Socialization, and Taxpayer Compliance on State Tax Revenue (A Study of E-Commerce Players in Jakarta) - Pamela Colleen; Nurul Hidayah (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This research was conducted to determine the influence of PMSE tax policy, tax socialization, and taxpayer compliance on state tax revenue, with a study on e-commerce actors in Jakarta. This research uses a quantitative approach. The analysis methods used are PLS-SEM analysis and Logistic Regression using SmartPLS 3.0 software. Based on the research results, the study shows that the PMSE tax policy variable has a negative and insignificant effect on state tax revenue. The tax socialization and taxpayer compliance variables have a positive and significant effect on state tax revenue.